Anthracene‐Assisted Morphology Optimization in Photoactive Layer for High‐Efficiency Polymer Solar Cells. (26th June 2021) - Fan, Hongyu; Yang, Hang; Wu, Yue; Yildiz, Okan; Zhu, Xianming; Marszalek, Tomasz; Blom, Paul W.M.; Cui, Chaohua; Li, Yongfang
Abstract: Currently, morphology optimization methods for the fused‐ring nonfullerene acceptor‐based polymer solar cells (PSCs) empirically follow the treatments originally developed in fullerene‐based systems, being unable to meet the diverse molecular structures and strong crystallinity of the nonfullerene acceptors. Herein, a new and universal morphology controlling method is developed by applying volatilizable anthracene as solid additive. The strong crystallinity of anthracene offers the possibility to restrict the over aggregation of fused‐ring nonfullerene acceptor in the process of film formation. During the kinetic process of anthracene removal in the blend under thermal annealing, donor can imbed into the remaining space of anthracene in the acceptor matrix to form well‐developed nanoscale phase separation with bi‐continuous interpenetrating networks. Consequently, the treatment of anthracene additive enables the power conversion efficiency (PCE) of PM6:Y6‐based devices to 17.02%, which is a significant improvement with regard to the PCE of 15.60% for the reference device using conventional treatments. Moreover, this morphology controlling method exhibits general application in various active layer systems to achieve better photovoltaic performance. Particularly, a remarkable PCE of 17.51% is achieved in the ternary PTQ10:Y6:PC71 BM‐based PSCs processed by anthracene additive. The morphology optimization strategy established in this work can offer unprecedented opportunities to build state‐of‐the‐art PSCs. Abstract : A universal morphology optimization method is developed by applying anthracene as a solid additive to improve the photovoltaic performance of polymer solar cells. Anthracene can restrict the over‐aggregation of nonfullerene acceptors during the film‐forming process, and then facilitate bicontinuous phase separation during the kinetic process of its removal in the blend under thermal annealing.